O papel dos proteoglicanos na adesão celular durante a tumorigênese: um modelo in vitro para o estudo da interação câncer-estroma - Vicente, Carolina Meloni [UNIFESP] (2009)
During metastasis cells lose their original tissue contacts, move through the extracellular matrix (ECM), enter the lymphatic and/or blood system, extravasate and subsequently form new tumors. Therefore, these tumor cells must experience changes in cell-ECM adhesion. Adhesion receptors play crucial roles in the neoplastic transformation of normal cells through the induction of cancer-specific cellular behavior and morphology. This implies that cancer cells likely express and utilize a distinct set of adhesion receptors during carcinogenesis. Syndecan-2 is a transmembrane heparan sulfate (HS) proteoglycan which has been implicated in the formation of specialized membrane domains and functions as a direct link between the extracellular environment and the organization of the cortical cytoplasm. In several colon-rectal cancer cell lines, syndecan-2 is highly expressed compared to normal cell lines. This increase appears to be critical for cancerous cell behavior since it regulates adhesion and proliferation and therefore the tumorigenic activity. The results of this study showed that in a highly metastatic colon-rectal cancer cell line, HCT-116, both expression and synthesis of syndecan-2 are enhanced when grown on ECM produced by fibroblasts. The expression of the others syndecans decreased, as did HS in the ECM produced by the cancer cells. Among the stromal components of ECM, the fibronectin was shown to be important for the increase of syndecan-2. Co-localization between syndecan-2, integrin ƒÑ5ƒÒ1 and fibronectin, suggests the involvement of these molecules in the adhesion mechanism of HCT-116 cells. Furthermore, blocking syndecan-2 with an antibody resulted in the absence of stress fibers during cell adhesion, indicating its important role in the regulation of actin filaments. Thus, the stromal ECM has a fundamental role in regulating the expression of cell surface proteins and probably signaling to the interior of cancer cells by altering their proliferation and adhesion, and its format.